Printability of paper and paperboard surface treatment with gum rosin and derivatives - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose This study aims to provide control of liquids, especially against water-based ink on the paper and paperboard surface with natural substances, in also practical and greenway. Design/methodology/approach The paper surface was treated with natural rosin and its derivatives to obtain a hydrophobic effect and to improve printing properties. The oleoresin samples collected from Pinus nigra Arnold and Pinus pinaster Aiton trees in the controlled area and turpentine content removed was by hydrodistillation. The gum rosin (GR), fortified 10% with maleic anhydride (MGR) and esterified with 10% pentaerythritol (PMGR) samples solved in a simply alcohol and sprayed the base paper surface directly with a spray gun. Base paper samples were paperboard, bleached paper and test liner paper. Then, flexo printing was applied and printability properties were measured. Findings The treatment weights of these paper samples were 1.8 +/- 0.5, 1.3 +/- 0.5 and 0.7 +/- 0.2 g/m(2), respectively, compared to the base paper. Greater Cobb60 results were obtained from modified rosin samples than unmodified gum rosin-sized paperboards and the PMGR surface treatment reduces Cobb60 values by 20% and MGR treatment reduces 15% comparing to the base sheet. Then, the printing procedure was applied to the surface of the treated materials using a flexo printing system. As a result of the treatment better print density, chroma and print lightness value consumed a less hydrophobic agent and controlling water-based flexo ink on the base paper surface. Originality/value The unique aspect of this work was improving the hydrophobicity of the paper surfaces was achieved by spraying with natural rosin and derivatives.
Keywords: Printability; Flexo; Gum rosin; Water-based ink; INK; CELLULOSE; PIGMENTS